SUITABILITY INDEX of MANGROVE ECOTOURISM IN MALANG REGENCY - Nuddin Harahab; Setiawan Setiawan (Faculty of Fisheries and Marine Science, Brawijaya University, 2017)
Recently mangrove ecosystems are constantly under pressure as a result of various human activities. Utilization of mangrove forests fullest possible without damaging the forest ecosystem is one of them is for recreation limited by means of ecotourism. The purpose of this study was to determine and analyze the suitability of mangrove eco-tourism in the regency of Malang. The method used in this research is descriptive method, using the techniques of research interviews and observation. The results showed that the mangrove vegetation found in the South Beach regency of Malang, there stands the main mangrove species, namely the Sonneratia alba, Rhizophora mucronata. Suitability index mangrove area for ecotourism activities in the South Coast Malang included in the appropriate category. Keywords : mangrove, ecotourism, index, mangrove utilization